2015
DOI: 10.2334/josnusd.57.345
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Strength of Recommendation Taxonomy (SORT) to assess full-mouth treatments of chronic periodontitis

Abstract: Previous studies have not resolved whetherscaling and root planing with a full-mouth (with or without antiseptics) or quadrant approach is better for treatment of chronic periodontitis. We identified relevant studies and used Strength of Recommendation Taxonomy (SORT) criteria to critically interpret the results of all relevant studies. A literature search was performed using the PubMed, EMBASE, and Cochrane databases up to July 2015. Selected studies were stratified according to their quality, quantity, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…In fact, patient-oriented outcomes that measure changes in end points that really matter to patients, such as esthetics, QoL, and pain relief, provide better evidence than disease-oriented outcomes such as probing depth reduction. [ 19 ] As CP and DM2 clearly affect the general health of individuals, the use of such questionnaires seems to be of interest to study the consequences of both diseases in terms of well-being and QoL. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patient-oriented outcomes that measure changes in end points that really matter to patients, such as esthetics, QoL, and pain relief, provide better evidence than disease-oriented outcomes such as probing depth reduction. [ 19 ] As CP and DM2 clearly affect the general health of individuals, the use of such questionnaires seems to be of interest to study the consequences of both diseases in terms of well-being and QoL. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Vale salientar que a maioria dos artigos não avaliou o índice de placa e índice gengival (Paolantonio et al, 2008;Javed & Kohli, 2010;Goodson et al, 2012;Faggion et al, 2014;Tabenski et al, 2017;Machtei et al, 2021), talvez porque o foco dos trabalhos fosse avaliar a eficácia do dispositivo na redução da bolsa periodontal que é uma sequela da periodontite. Porém, é importante ressaltar que o sucesso do tratamento periodontal depende da qualidade do controle do biofilme supragengival feito pelo paciente (Canabarro et al, 2015). Estudos anteriores mostraram que a falta deste controle no início do tratamento, ou seja, antes do controle do biofilme subgengival pelo profissional, pode comprometer o sucesso do tratamento da periodontite em médio e longo prazo (Ximénez-Fyvie et al, 2000;Eberhard et al, 2008).…”
Section: Discussionunclassified
“…It was found that the consumption of probiotic or conventional milk drinks associated with NSPT effectively reduced the pocket depth and gained periodontal attachment. The effectiveness of NSPT in reducing clinical parameters of periodontitis has already been established (Canabarro et al, 2015;Heitz-Mayfield et al, 2002) and is associated with the initial reduction in the number of pathogenic bacteria and the interference in the bacterial composition of the biofilm (Morales et al, 2018). However, pathogen reduction appears to be transient, even when the therapy is combined with antiseptics or antibiotics (Teughels et al, 2013).…”
Section: Discussionmentioning
confidence: 99%